« Les interests du sexe » : dédicataires féminins et réseaux de sociabilité chez Marie de Gournay - Beaulieu, Jean-Philippe; Fournier, Hannah (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2004)
Even though Marie de Gournay's (1565-1645) numerous texts contain only a few direct references to the activities of the "salons" in the first half of the seventeenth century, they show ample evidence of the author's presence in public and social life. Through anecdotes, allusive references and dedications to prominent people she knew (or wished to know), Gournay reveals the complex web of relationships of which she was part. Not only do her collected works (Advis, 1641) suggest her association with public figures known to attend notorious "salons," they invite us to broaden our view of sociability, defined mostly, according to Gournay, in terms of intellectual endeavours and affinities. Describing herself as an active member of an intellectual community (formed mostly by well-known women), Gournay validates her life, work and ambitions through feminine solidarity-real or virtual.